Antifungal Pipeline - McCarty, Todd Patrick; Pappas, Peter G. (Frontiers in Cellular and Infection Microbiology, 2021)
In many ways, fungal diseases are forgotten or neglected. Given the significantly lower frequency compared to similar bacterial etiologies across the spectrum of infectious syndromes, it makes sense that anti-bacterial agents have seen the bulk of development in recent decades. The vast majority of new antifungal medications approved for use in the past 10 years have been new versions in the same class as existing agents. Clinical mycology is crying out for new mechanisms of action in the setting of rising resistance and emergence of new organisms. Fortunately, this trend appears to be reversing. There are numerous agents in advanced stages of development offering novel dosing regimens and mechanisms of action to combat these threats. Herein we review seven antifungal agents that we hope to see come to market in the coming years to aid physicians in the treatment of mucocutaneous and invasive fungal infections.